Performance evaluation of a direct water-injected gasifier utilizing low-grade Philippine coals - Clar, Jose D.
This study was conducted to determine the feasibility of utilizing low-grade Philippine coals as substitute or augmentation fuel in an experimental set-up consisting of a direct water-injected gasifier which was close coupled to an oil-fired furnace by means of producer gas burner. The study focused on the effects of the use of liquid water, instead of steam, in the gasification of low-grade coals. The study included the formulation of a mathematical model and computer simulation procedures which could be used to predict the performance of the experimental set-up using the regular coal analysis and a few operational parameters. The experiments have shown that liquid water could be used instead of steam to prevent clinkering of the ash and also to improve gas quality.